Толерантность в социальных сетях во время обучающего процесса как показатель качества коммуникации между субъектами образовательной среды - Квасник, Ольга Витальевна (Impressum, 2020)
The article considers the rating of social networks among Ukrainian stakeholders, including the conditions for their use, at the time of 2019 mainly among students or adults, the semantic meaning of the concept of tolerance is disclosed, its meaning for interaction in a social network is clarified, the effectiveness of using a social network for high-quality communication between the subjects of the educational process and proved the rationality of using innovative technologies to improve the education level of future ma histres.
Keywords: качество образования; толерантность; эффективность коммуникации; социальная сеть; инновационные технологии; использование доступных технических средств